Physiological mechanisms and phytoremediation potential of the macrophyte Salvinia biloba towards a commercial formulation and an analytical standard of glyphosate - da Silva Santos, Jaqueline (2020)
Glyphosate (Gly) is the most widely used herbicide in the world and has broad-spectrum and non-selective activity. Its indiscriminate use hence risks contamination of water bodies and can affect living organisms, especially sensitive or resistant non-target plants. Despite this, studies on physiological mechanisms and Gly remediation in Neotropical aquatic plants remain limited. This study aims to evaluate the physiological mechanisms of the aquatic macrophyte Salvinia biloba on exposure to different concentrations of a Gly commercial formulation (Gly-CF) and a Gly analytical standard (Gly-AS). Furthermore, using square-wave voltammetry (SWV), we determined whether the studied plant could remove Gly from water. Our data suggest that Gly-AS and Gly-CF induce similar physiological responses in S. biloba. However, Gly-CF was more phytotoxic. Depending on the concentration, the two forms of Gly affected the plants, decreasing the chlorophyll a and b contents and the photosystem II (PSII) photochemical activity. The data also revealed that Gly promoted oxidative stress and increased the shikimic acid concentration. At the same time, the plants removed Gly from water, with 100% removal for 1 mg L−1 Gly and above 60% removal for the other concentrations studied. Therefore, our results suggest that S. biloba may be a potential phytoremediation agent for low Gly concentrations, since 1 mg L−1 Gly was completely removed and exhibited low phytotoxicity. This study deepens our scientific understanding of the Gly impact on and the phytoremediation potential of S. biloba.